Cost-effectiveness of FOLFIRI + cetuximab vs FOLFIRI + bevacizumab in the first-line treatment of RAS wild-type metastatic colorectal cancer in Germany: data from the FIRE-3 (AIO KRK-0306) study. (3rd May 2020) - Stintzing, Sebastian; van Oostrum, Ilse; Pescott, Chris P.; Ronga, Philippe; Heeg, Bart; Heinemann, Volker
Abstract: Aims: This analysis evaluates the cost-effectiveness of first-line treatment with FOLFIRI + cetuximab vs FOLFIRI + bevacizumab for patients with RAS wild-type (wt) metastatic colorectal cancer (mCRC) in Germany based on the randomized phase 3 FIRE-3 trial. For patients with RAS wt mCRC, FOLFIRI + cetuximab yielded statistically significant median overall survival gains over FOLFIRI + bevacizumab. Materials and methods: A standard 3-state partitioned survival cost-utility model was developed to compare the health benefits and costs of treatment from a German social health insurance perspective using individual patient–level trial data. Health outcomes were reported in life-years (LYs) and quality-adjusted life-years (QALYs) gained. Survival was estimated based on Kaplan-Meier (KM) curves supplemented with best-fitting parametric survival model extrapolations. Subgroup analyses of patients with a left-sided primary tumor location or patients with metastases confined to the liver were performed. Results: In the modified intention-to-treat analysis, FOLFIRI + cetuximab, providing 0.68 additional LYs (0.53 QALYs), yielded incremental cost-effectiveness ratios (ICERs) of €36, 360/LY and €47, 250/QALY. In subgroup analyses, patients experienced improved survival gains without a corresponding increase in costs, resulting in lower ICERs. Our model was most sensitive to changes in treatment duration across all lines of therapy, utility of progressive disease, as well as patients' weight and body surface area. Limitations: This cost-effectiveness analysis was based on patient-level data from the FIRE-3 trial. Trial outcomes may not adequately reflect those in the real-world setting. Additionally, resource use and costs were obtained from tariff lists, which do not account for differences in treatment practice. These considerations limit generalizability of outcomes to other countries, or within the German healthcare setting. Conclusions: Based on our analyses, FOLFIRI + cetuximab is cost-effective compared with FOLFIRI + bevacizumab in patients with RAS wt mCRC, with ICERs well below willingness-to-pay thresholds for diseases with a high burden.